Payment for environmental services in agricultural landscapes economic policies and poverty reduction in developing countries - Lipper, Leslie; Food and Agriculture Organization of the United Nations (Rome, Italy Food and Agriculture Organization of the United Nations [New York] Springer, 2009)
In recent years, development policy has responded to an increasing concern about natural resource degradation by setting up innovative payment for environmental services (PES) programs in developing countries. PES programs use market and institutional incentives in order to meet both environmental and poverty alleviation objectives. However, their optimal design, implications for the rural poor, and how these initiatives integrate into international treaties on global warming and biodiversity loss are still being discussed. This book addresses these issues by examining analytical tools, providing policy insights and stimulating debate on linkages between poverty alleviation and environmental protection. In particular, it turns attention towards the role of environmental services in agricultural landscapes as they provide a living for many poor in developing countries.--Publisher's description.
Introduction and overview / Randy Stringer, ... [et al.] -- Putting payments for environmental services in the context of economic development / Leslie Lipper, Nancy McCarthy and David Zilberman -- Designing payments for environmental services with weak property rights and external interests / Stefanie Engel and Charles Palmer -- Marketing environmental services / Amir Heiman, Yanhoung Jin and David Zilberman -- Economics of carbon sequestration projects involving smallholders / Oscar Cacho -- Conservation payments to reduce wildlife habitat fragmentation and disease risks / Richard D. Horan, Jason F. Shogren and Benjamin M. Gramig -- Payments for ecosystem services, poverty and sustainability : the case of agricultural soil carbon sequestration / John M. Antle and Jetse J. Stoorvogel -- Lessons learned from Mexico's payment for environmental services program / Jennifer Alix-Garcia, ... [et al.] -- Agricultural landscape externalities, agro-tourism, and rural poverty reduction in Morocco / Khalil Allali -- Exploring environmental services incentive policies for the Philippines rice sector : the case of intra-species agrobiodiversity conservation / Nobuhiko Fuwa and Asa Jose U. Sajise -- Assessing the feasibility of wetlands conservation : using payments for ecosystem services in Pallisa, Uganda / Imelda Nalukenge, John Antle, and Jetse Stoorvogel -- Managing wildlife damage to agriculture in Bhutan : conflicts, costs and compromise / Karma Ura, Randy Stringer and Erwin Bulte -- Conclusion / David Zilberman.
Includes bibliographical references and index.
Keywords: Agriculture and state -- Developing countries; Agricultural industries -- Government policy -- Developing countries -- Finance; Agricultural industries -- Environmental aspects -- Developing countries; Sustainable agriculture -- Developing countries; Poverty -- Government policy -- Developing countries; Developing countries -- Economic policy